2012
DOI: 10.1097/hjh.0b013e328358faf7
|View full text |Cite
|
Sign up to set email alerts
|

Greater cardiovascular reactivity to a cold stimulus is due to higher cold pain perception in black Africans

Abstract: Black Africans display a more pronounced cold pressor test-induced rise in heart rate and blood pressure, which may be explained by greater pain-related increments in blood pressure. A higher cognitive appraisal of pain and a blunted baroreflex-mediated dampening of autonomic structures may contribute to the exaggerated blood pressure reactivity in black Africans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Identifying effective treatments and interventions for modifiable factors, such as chronic stress (eg, anxiety, depression), that modulate mechanisms associated with higher asleep BP among blacks compared with whites (eg, disturbances in autonomic function, altered sodium excretion) may help reduce racial differences in BP during sleep. 1014 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying effective treatments and interventions for modifiable factors, such as chronic stress (eg, anxiety, depression), that modulate mechanisms associated with higher asleep BP among blacks compared with whites (eg, disturbances in autonomic function, altered sodium excretion) may help reduce racial differences in BP during sleep. 1014 …”
Section: Discussionmentioning
confidence: 99%
“…714 A meta-analysis of 18 studies reported higher asleep BP and less BP dipping among blacks compared with whites. 15 However, the definition of asleep BP dipping was inconsistent across studies (eg, as the absolute or relative differences in awake and asleep BP levels).…”
Section: Introductionmentioning
confidence: 99%
“…The current results should be viewed in light of several limitations. First, the magnitude of the blood pressure response to cold stress is related to pain intensity, perception, and appraisal (Peckerman et al., ; Reimann et al., ). The current study has collected no information on pain.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the perception of pain during the CPT, however, must also not be underestimated as it could elevate blood glucose levels through the release of b-endorphins, stimulating hyperglycemia [11,24,25]. Reimann et al [11] reported that black Africans show a more pronounced CPT-induced increase in heart rate and blood pressure, which may be attributed to greater pain-related increments in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed a-adrenergic and b-adrenergic stimulation elicits a myocardial reaction through central mechanisms, whereas a-adrenergic stimulation elicits a vascular response pattern through vascular mechanisms [9,10]. The CPT also produces a pain stimulus, releasing b-endorphins which have a hyperglycemic effect [11]. The CPT elicits sympathetically mediated spontaneous vasoconstriction with subsequent increases in total peripheral resistance (TPR), cardiac afterload, and diastolic blood pressure (DBP) [12].…”
Section: Introductionmentioning
confidence: 99%